Impact of rearing systems in the Eastern Amazon on cholesterol, β-carotene and vitamin E homologues in steer - dos Santos Miranda Lobato, Adriny; da Silva, Jamile Andrea Rodrigues; de Carvalho Rodrigues, Thomaz Cyro Guimarães; Silva, André Guimarães Maciel e; da Cruz, Andrea Viana; Ferreira, Ana Paula Damasceno; Costa, Mónica Mendes; Cunha, Antonio Marcos Quadros; Lourenço-Costa, Vanessa Vieira; Barbosa, Antônio Vinícius Corrêa; Prates, José António Mestre; de Brito Lourenço-Júnior, José (Frontiers in Veterinary Science, 2024)
The quality of meat, with a focus on compounds important for human health, is directly related to the rearing systems in which the animals are produced. The search for a balanced diet, with an emphasis on low cholesterol and adequate levels of vitamins, aligns with society's emphasis on healthy eating, directly correlated with the importance of the offer made by producers for the cattle's diet. The objective was to verify the impact of different rearing systems, in the Eastern Amazon, during the rainy season, on the concentrations of vitamins (A, E) and cholesterol in the muscle (Longissimus lumborum) of crossbred Nelore cattle, castrated, aged between 24 and 36 months, and weighing between 410 and 628 kg. Twelve animals, from each of the three pasture rearing systems: native pasture in flooded areas of Monte Alegre; native pasture in a flooded area of Santa Cruz do Arari; and pasture cultivated on dry land in São Miguel do Guamá, all located in Pará, Brazil -were sampled in commercial slaughterhouses. A notable influence was observed in the concentrations of β-carotene (p<0.01), α-Tocopherol (p=0.02), β-Tocopherol (p<0.01) and the combined sum of β-Tocotrienol and γ-Tocopherol (p <0.01), as well as δ-Tocopherol (p <0.01) when contrasting extensive with intensive systems (confinement). However, there was a difference in the content of vitamins and cholesterol between the isolated extensive systems, or between the four rearing systems (p>0.05). Extensive systems, mainly in Monte Alegre, demonstrated greater amounts of α-Tocopherol and δ-Tocopherol.On the other hand, the intensive system exhibited higher levels of other investigated compounds, clarifying the nutritional variations generated by different livestock rearing practices in the region.Therefore, the results obtained are innovative in the Eastern Amazon, Brazil, in addition to inspiring the development of new research to meet other demands in this field, and achieve additional results, such as determining which meat, coming from cattle in production systems in the country, presents the better compositional quality of vitamins and lipids.